Journal Influence on the Design of Finance Doctoral Education. - Corrado, Charles J; Ferris, Stephen P (Journal of Finance, 1997)
This article surveys the influence of research journals on finance doctoral education. Influence is measured by citations from syllabi of finance seminars. A sample of 101 distinct syllabi submitted by thirty-three finance doctoral programs yields a list of 1,031 articles cited by at least two schools. These 1,031 articles generate 3,273 citations referencing seventeen finance, economics, and accounting journals, where multiple citations from a single school are counted as a single citation. The most notable findings are the wide variety of seminar content across finance doctoral programs and the dominance of five finance journals in providing this diverse content.